The Effect of Dabigatran on Select Specialty Coagulation Assays - Adcock, Dorothy M.; Gosselin, Robert; Kitchen, Steve; Dwyre, Denis M. (American journal of clinical pathology, 2013)
Dabigatran etexilate is a new oral anticoagulant that functions as a direct thrombin inhibitor. An inhibitor of thrombin has the potential to interfere with essentially all clot-based coagulation assays and select chromogenic assays, whereas the drug would not be expected to interfere in antigen-based assays. The purpose of this study was to evaluate the effect of dabigatran on various specialized coagulation assays using normal plasma specimens with varying concentrations of dabigatran (the active form of dabigatran etexilate). We have demonstrated that samples containing therapeutic levels of dabigatran may lead to underestimation of intrinsic factor activities with abnormal activated partial thromboplastin time (aPTT) mixing study results and a false-positive factor VIII Bethesda titer; overestimation of protein C and protein S activity and activated protein C resistance ratio when determined using aPTT-based methods; and overestimation of results based on chromogenic anti-IIa assays but no effect on antigen assays and select chromogenic assays.